Influence of orientation on ordered microstructure of PAN-based fibers during electron beam irradiation stabilization - Shin, Hye Kyoung; Park, Mira; Kim, Hak-Yong; Park, Soo-Jin (Journal of industrial and engineering chemistry (Seoul, Korea), 2015)
This work evaluated the effect of various amounts of tension on polyacrylonitrile (PAN) precursor fibers during electron beam irradiation (EBI) stabilization. X-ray diffraction (XRD), tensile testing, and scanning electron microscopy (SEM) were implemented to determine the effects of tension on the PAN fibers. During the stabilization process, the fibers shrunk due to a loss of molecular alignment, and the addition of tension acting on the PAN fibers during stabilization was proposed to address this issue. In this work, PAN fibers were stabilized by EBI under various loads. It was found from the XRD data that tension led to the development of crystalline structures during EBI stabilization. From the tensile test, it was found that tension led to a small increase in strength due to conversion of disordered structures into ordered structures in the fibers.